(NkOMPOZITORI bUKOWINI (B:s (NdOW)QÆDNIK(B-(NPOSÆBNIK (B/s)E - (N~nu )QÆM(B. (N`(B.(NfEDXKOWI^As)E ((N~ERN)QÆWCÆ (B:s)E (NrUTA(B,s, 2006)
(NdOW)QÆDNIK(B-(NPOSÆBNIK PODAÃ WÆDOMOSTÆ PRO TWOR^U TA PEDAGOGÆ^NU DÆQLXNÆSTX KOMPOZITORÆW ~ERNÆWECXKOÇ OBLASTÆ(B. (NdLQ STUDENTÆW Æ WIKLADA^ÆW MUZI^NIH Æ MUZI^NO(B-(NPEDAGOGÆ^NIH SPECÆALXNOSTEJ WUZÆW(B, (NU^ITELÆW MUZI^NIH Æ ZAGALXNOOSWÆTNÆH [KÆL(B.s)E
Keywords: (NdWORSXKIJ(B, (NpAWLO aNAN)QÆJOWI^(B,s)E -- (NR(B. (NN (B1953s; (NmOZGOWIJ(B, (NmIKOLA pETROWI^(B,s -- 1947-2010 (NRR(B.s; (NsMALX(B, (NkUZXMA aNTONOWI^(B,s -- 1935-2012 (NRR(B.s; (NmUZIKAs -- (N~ERN)QÆWECXKA OBLASTX (B((NuKRAÇNA(B).s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E